Pengaruh Kebijakan Dividen terhadap Harga Saham (Studi pada Perusahaan Pertambangan di Bursa Efek Indonesia 2008-2012) - Irma Kurnia Fitri; Imas Purnamasari (Universitas Winaya Mukti, 2018)
Dividend policy is a decision that can be taken by the company in deciding whether the profit earned will be distributed in the form of dividends or retained for reinvestment. Bonuses could be used as a signal by investors to make investment decisions that will affect the company's stock price. The main purpose of this study is to identify whether dividend policy could convey information to the market which generates a reaction on stock prices. Research methods used descriptive and verification. An indicator of dividend policy was the dividend payout ratio, and stock prices used in this study was the closing share price. Samples in this study were ten mining companies on the Indonesia Stock Exchange that regularly pay dividends in 2008-2012. Analysis of the data used was a simple linear regression. Based on the research showed that the dividend policy affected stock prices.